2008
DOI: 10.1083/jcb.200709076
|View full text |Cite
|
Sign up to set email alerts
|

The interaction of IQGAP1 with the exocyst complex is required for tumor cell invasion downstream of Cdc42 and RhoA

Abstract: Invadopodia are actin-based membrane protrusions formed at contact sites between invasive tumor cells and the extracellular matrix with matrix proteolytic activity. Actin regulatory proteins participate in invadopodia formation, whereas matrix degradation requires metalloproteinases (MMPs) targeted to invadopodia. In this study, we show that the vesicle-tethering exocyst complex is required for matrix proteolysis and invasion of breast carcinoma cells. We demonstrate that the exocyst subunits Sec3 and Sec8 int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
314
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 261 publications
(340 citation statements)
references
References 61 publications
(87 reference statements)
21
314
0
2
Order By: Relevance
“…Matrix metalloprotease accumulation at specific points of contact may require polarized vesicle trafficking. Recently, Chavrier and collaborators showed that the exocyst regulates the exocytosis of matrix metalloproteases in invasive breast carcinoma cells in combination with the Cdc42 effector IQGAP1, the expression of which is highly increased in a variety of cancers (Rittmeyer et al, 2008;Sakurai-Yageta et al, 2008).…”
Section: Hijacking Of the Domain-identity Machinerymentioning
confidence: 99%
“…Matrix metalloprotease accumulation at specific points of contact may require polarized vesicle trafficking. Recently, Chavrier and collaborators showed that the exocyst regulates the exocytosis of matrix metalloproteases in invasive breast carcinoma cells in combination with the Cdc42 effector IQGAP1, the expression of which is highly increased in a variety of cancers (Rittmeyer et al, 2008;Sakurai-Yageta et al, 2008).…”
Section: Hijacking Of the Domain-identity Machinerymentioning
confidence: 99%
“…Elimination of the activities of Rac1 or Cdc42 results in a reduction of invadopodia formation in glioma cells and mammary carcinoma cells, respectively [197,215]. On the other hand, RhoA is known to be important for actin assembly and exocytosis of MMP in invadopodia by controlling IQGAP1 activity [216]. For more detailed insights into invadopodia formation and function, we refer the reader to several excellent recent reviews [188,[217][218][219].…”
Section: Podosomes and Invadopodiamentioning
confidence: 99%
“…However, they are most likely to involve microtubuledependent trafficking of vesicles from the Golgi. Indeed, the Golgi is always observed in close proximity to invadopodia (Buccione et al, 2004;Ayala et al, 2006), and parts of the machinery for vesicle docking and fusion, such as the v-SNARE VAMP7 (Steffen et al, 2008) or the exocyst complex (Sakurai-Yageta et al, 2008), are required for MT1-MMP accumulation at invadopodia. In addition, MMP recruitment at invadosomes seems to involve parts of the actin cytoskeleton, most notably cortactin .…”
Section: Matrix Degradationmentioning
confidence: 99%